A DOPO-based phosphorus-nitrogen flame retardant bio-based epoxy resin from diphenolic acid: Synthesis, flame-retardant behavior and mechanism. (June 2020) - Chi, Zhiyuan; Guo, Zongwei; Xu, Zice; Zhang, Mengjie; Li, Ming; Shang, Lei; Ao, Yuhui
Abstract: Searching a renewable and flame-retardant alternative to bisphenol A epoxy resins is a necessary development trend. Diphenolic acid, a plant derivative, has been proven to be one of the sustainable alternatives to bisphenol A. However, how to impart the flame-retardant property to diphenolic acid thermosets is still a challenge to synthesize high performance intrinsic flame-retardant bio-based epoxy resins. A flame-retardant bio-based epoxy resin (TEBA) was designed and synthesized via a three-step synthetic pathway from 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO)、diethanolamine and diphenolic acid (DPA). The chemical structures of the intermediate and final products were confirmed by 1 HNMR and FTIR spectroscopy. TEBA cured with 4, 4′-diaminodiphenylmethane (DDM) curing agent was compared with a standard bisphenol A epoxy resin (DGEBA). Due to the combination of phosphorus and nitrogen in the main chain, the TEBA-DDM shows superior flame retardancy. Compared with DGEBA-DDM, LOI of TEBA-DDM increased from 25.8% to 42.3%, UL-94 test rating from no rating to V-0 rating, self-extinguishing within 3s. The peak heat release rate (PHRR) in the cone calorimetry test decreased by 67%. total heat release (THR) and total smoke generation (TSP) decreased by 27% and 35%, respectively. In addition, the flame retardant mechanism of TEBA epoxy thermosets was researched by FTIR, residual char photograph, SEM, TG-IR analysis and Raman spectroscopy. Meanwhile, TEBA-DDM and DGEBA-DDM have comparable mechanical properties. Highlights: The main raw materials come from bio-based, which saves fossil resources. Direct synthesis of intrinsic flame retardant resins, unlike additive and co-curing formulations. Design of phosphorus-nitrogen combination flame retardant structure, excellent flame retardancy. A comprehensive and detailed discussion of the flame retardant mechanism.